Assessing easy-injured characteristics of drought on socio-economic development in Central Highland by Socio-economic Drought Vulnerability index - Huong, Le Van; Hoang, Phi Thi Thu (Vietnam Journal of Earth Sciences, 2014)
Drought in Central Highland occurs frequently in the dry season and cause serious damage to socio-economic development in this region. The authors use Socio-economic drought vulnerability index (SDI) to assess impacts of drought on socio-economic development. It is new assessment method. We calculated three component indexes: IDI (income diversification index), EDI (employment diversification index) and CDI (crops range index) for assessment of SDI. Among those, CDI was very complicated to calculate. Dak Lak province had maximum agriculture economics by IDI and SDI index and, EDI index was also quite high, But Kon Tum province had the minimum of SDI and the economics development was more harmonious than others. The number of agriculture labors for all provinces of the region made up over 70% total labor. On the based of study, we also proposed some solutions for drought reduction and prevention in Central Highland region.